Transformation of cryovacuum condensates of ethanol near the glass transition temperature - Aldiyarov, A.; Kadylbek, S.; Zhumabayeva, S. (Recent Contributions to Physics, 2014)
Infrared spectrometry and thermodesorption experiments with thin films of ethanol cryovacuum condensates formed during condensation of the gas at different pressures and temperatures on a cooled metal substrate. The main purpose was to study the dynamical relaxation processes in the vicinity of the glass transition temperature and the transition from orientationally disordered to ordered states in thin films of ethanol cryocondensates. It was found that the films of ethanol cryocondensates formed during the condensation at the T = 16 K were in an amorphous state (ASE). An increase in the sample temperature leads at T = 80 K to a transformation of the ASE into a structural glass. Further heating to T = 97 K was ac-companied by a transformation of the structural glass into a supercooled liquid, and then,at T = 105 K to a plastic crystal.
Keywords: supercooled liquid; plastic crystal; mono-clinic crystal; glass transition temperature; IR spect-rum